2015
DOI: 10.3390/cells4040706
|View full text |Cite
|
Sign up to set email alerts
|

Complex Commingling: Nucleoporins and the Spindle Assembly Checkpoint

Abstract: The segregation of the chromosomes during mitosis is an important process, in which the replicated DNA content is properly allocated into two daughter cells. To ensure their genomic integrity, cells present an essential surveillance mechanism known as the spindle assembly checkpoint (SAC), which monitors the bipolar attachment of the mitotic spindle to chromosomes to prevent errors that would result in chromosome mis-segregation and aneuploidy. Multiple components of the nuclear pore complex (NPC), a gigantic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 145 publications
(227 reference statements)
4
11
0
Order By: Relevance
“…These data support previous studies in humans and other organisms that have shown that MAD1L1 associates with TPR, NUP153, and NUP107 and is important for generating the MAD1L1-MAD2L1 complex in early mitosis to establish the SAC (62)(63)(64)(65)(66)(67)(68). Similarly, MAD2L1 was found to associate with TPR (previously verified in (63), NUP50, Nup153, NUP210 and ELYS (supplemental Fig.…”
Section: Analysis Of Core Sac Protein-kinetochore Protein Proximity Asupporting
confidence: 90%
“…These data support previous studies in humans and other organisms that have shown that MAD1L1 associates with TPR, NUP153, and NUP107 and is important for generating the MAD1L1-MAD2L1 complex in early mitosis to establish the SAC (62)(63)(64)(65)(66)(67)(68). Similarly, MAD2L1 was found to associate with TPR (previously verified in (63), NUP50, Nup153, NUP210 and ELYS (supplemental Fig.…”
Section: Analysis Of Core Sac Protein-kinetochore Protein Proximity Asupporting
confidence: 90%
“…One possibility to explain these findings is to consider that MAD2 plays a role controlling the translocation of DNA damage repair proteins to the nucleus [27] . In agreement with these results, MAD2 has been shown to be localized at the nuclear pore during interphase and to interact with TRp1 and Nup153 proteins [28] . For instance, in a work performed using HeLa cells, it was demonstrated that MAD2 interacts with XPD and ERCC1, two key proteins that participate in nucleotide excision repair pathway (NER).…”
Section: Mad2 More Than a Mitotic Regulator?supporting
confidence: 79%
“…The duration of mitosis depends both on mitotic timers and on satisfaction of the spindle assembly checkpoint [68][69][70][71] . When a minimal time has elapsed and the last pair of chromosomes has been aligned at the metaphase plate (reviewed in REF.…”
Section: Mitotic Exitmentioning
confidence: 99%